Vitamin D knowledge, attitudes, practices and serum concentration among pregnant women attending a Malaysian tertiary hospital - Ibrahim, Yakubu; Mohd Jamil, Amilia Afzan; Basri, Nurul Iftida; Reen, Simran Lau Sher; Asmunni, Muhammad Daniel Iman; Govidarajoo, Nirosha (John Wiley and Sons Inc, 2025)
Vitamin D deficiency is increasingly recognized as a public health concern among pregnant women due to its association with adverse pregnancy outcomes. Inadequate knowledge, attitudes, and practices (KAP) related to vitamin D may contribute to this issue. The study aimed to evaluate the KAP and serum vitamin D concentration among pregnant women. The study was a hospital-based cross-sectional study involving pregnant women residing in the Klang Valley area. Relevant data on sociodemographic characteristics, knowledge, attitudes, practices, and physical activity were collected using a structured questionnaire. Blood samples were collected using the veni puncture technique, and serum vitamin D levels were measured using the electrochemiluminescence immunoassay (ELCIA) technique. There was a significantly higher proportion of participants with good knowledge as compared with participants with poor knowledge (54.1% vs. 45.9%); p = 0.015. There was a significantly higher proportion of participants with negative attitudes as compared with positive attitudes (54.8% vs. 45.2%); p = 0.0001 and inconsistent practice level (50.7% vs. 49.3%); p = 0.953. The prevalence of vitamin D deficiency was 64.4%. Further analysis revealed that non-Malay participants had significantly higher odds of having good knowledge of vitamin D compared to Malays (aOR = 0.420, p = 0.027). Employment status was significantly associated with good practices. Employed participants were two times more likely to demonstrate vitamin D-related practices (aOR = 2.036, p = 0.049) compared to their unemployed counterparts. There were no significant associations between sociodemographic characteristics and participants' attitudes on vitamin D. Despite the high levels of knowledge about vitamin D among the participants, the majority had negative attitudes, inconsistent practice levels, and a high prevalence of vitamin D deficiency. The findings underscore the need for policies and culturally acceptable strategies aimed at promoting attitudes and practices to prevent vitamin D deficiency in pregnancy.